Exploring the Potential of Intralesional Radiofrequency Ablation in Dermatology: A Case Series - Kanak Kusumika; Simran S Tuli; Vidyadhar R Sardesai (Wolters Kluwer Medknow Publications, 2024)
Intralesional radiofrequency (ILRF) ablation is a novel and safe dermatosurgical technique which, unlike conventional radiofrequency, minimizes the risk of epidermal scarring by precisely targeting the reticular dermis. ILRF's simplicity, cost-effectiveness, and cosmetic advantages make it an attractive option for treating various skin conditions. While ILRF has found applications in various fields beyond dermatology, there exists a scarcity of data concerning its safety and effectiveness in dermatology. We successfully utilized this novel technique to manage conditions such as lymphangioma circumscriptum and molluscum contagiosum, highlighting the promising impact and benefits of this approach.